OUT OF THE CLOSET AND UP THE LADDER? DIVERSITY IN ONTARIO’S BIG LAW FIRMS - Alkoby, Asher; Alon-Shenker, Pnina (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
While Canadian law generally provides protection against sexual orientation discrimination, and social acceptance is growing, there are some indications that LGBTQ lawyers face barriers relating to their sexual identity. Although more LGBTQ lawyers are now ‘out at work’, quantitative data is incomplete, and little is known about the actual experience of LGBTQ lawyers, who enter big firms in Ontario with the hope to advance through the ranks. This article begins to address this gap by providing qualitative analysis of the personal experience of LGBTQ lawyers entering the profession and the extent to which in-firm diversity initiatives shape their experience. Three main themes emerged from the interviews. First, racialized gay lawyers more consciously described their experiences at big law firms as negative and related it to their minority status. Second, the interviews offer insight into the ways in which gays and lesbians are forced to negotiate and perform their identity in a heteronormative workplace. Finally, the insights gleaned from the interviews suggest that the diversity programs devised by law firms may have helped diversify the lower ranks of law firms, but they seem to have failed to address the barriers that equity-seeking groups continue to face in retention and advancement through the ranks. The heteronormative organizational culture, as well as the promotion and compensation structures in firms continue to drive the composition of the leadership ranks and it arguably perpetuates homogeneity.